A composite index for measuring performance in higher education institutions. Issue 9 (30th September 2014) - Asif, Muhammad; Searcy, Cory
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Governments and funders are increasingly linking the funding of higher education institutions (HEIs) to their performance. Performance indicators (PIs) provide a means to measure and track performance of HEIs. The purpose of this paper is to provide a structured framework for mapping out key PIs and developing a composite index for measuring performance in HEIs. Design/methodology/approach – The paper makes use of the analytic hierarchy process to develop the framework. The application of the framework is demonstrated through a case study. Findings – A structured approach to determining key PIs and developing a composite index in HEIs is elaborated. The framework developed in this paper is consensus-based, knowledge-intensive, and allows input to and ownership of the decision process and its output. Practical implications – While there are numerous PIs; organizational resources and capabilities to manage these PIs are usually limited. HEIs must manage and improve their performance within their unique contexts. This paper provides a methodology to do so. Originality/value – The process of mapping out key PIs and developing composite indices for integrated performance measurement are not adequately understood and need further research. The framework discussed in this paper has not been elaborated on in previous publications.